2020
DOI: 10.1111/tpj.14755
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl methanesulfonate mutant library construction in Gossypium hirsutum L. for allotetraploid functional genomics and germplasm innovation

Abstract: SUMMARY As the gene pool is exposed to both strain on land resources and a lack of diversity in elite allotetraploid cotton, the acquisition and identification of novel alleles has taken on epic importance in facilitating cotton genetic improvement and functional genomics research. Ethyl methanesulfonate (EMS) is an excellent mutagen that induces genome‐wide efficient mutations to activate the mutagenic potential of plants with many advantages. The present study established, determined and verified the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…The mutation density of the 19 tobacco mutants tested in this study was one mutation per 19.3 kb and 18.0 kb of target regions in the WES and WGS datasets, respectively. These mutation densities are slightly higher than those reported for allotetraploid cotton and hexaploid wheat (one mutation per 26 kb and 24 kb, respectively; Slade et al, 2005 ; Lian et al, 2020 ), and more than 10-fold higher than those reported for diploid rice and tomato (one mutation per 294 kb and 367 kb, respectively; Till et al, 2007 ; Gupta et al, 2017 ). In allotetraploid tobacco, most genes have two functional copies referred to as homeologs.…”
Section: Discussioncontrasting
confidence: 63%
“…The mutation density of the 19 tobacco mutants tested in this study was one mutation per 19.3 kb and 18.0 kb of target regions in the WES and WGS datasets, respectively. These mutation densities are slightly higher than those reported for allotetraploid cotton and hexaploid wheat (one mutation per 26 kb and 24 kb, respectively; Slade et al, 2005 ; Lian et al, 2020 ), and more than 10-fold higher than those reported for diploid rice and tomato (one mutation per 294 kb and 367 kb, respectively; Till et al, 2007 ; Gupta et al, 2017 ). In allotetraploid tobacco, most genes have two functional copies referred to as homeologs.…”
Section: Discussioncontrasting
confidence: 63%
“…Genome-wide analyses of EMS-induced SNPs in virescent mutant line YL01 by resequencing revealed the ideal quality of the cotton EMS mutant library with the high and appropriate mutation density ( Table 1 ). Recently published EMS mutant library of Upland cotton [ 13 ] showed 85% of EMS SNPs occurred in intergenic region compared to 81.8% of our Sea island mutant library. In addition, our library quality was further assessed by taking into account 9.16% of the effective functional mutation in genic region compared to 8.3% of Upland cotton mutant library.…”
Section: Discussionmentioning
confidence: 86%
“…EMS-induced mutations in Upland cotton has been used to generate new valuable alleles and traits, leading to development of commercial cultivated varieties [ 6 , 9 , 10 , 11 , 12 ]. Recently, EMS-induced mutant libraries have been constructed in Upland cotton [ 13 ] representing beneficial genetic variations. Such collection of mutants represented a broad repertoire of mutants, that may serve as a valuable resource for functional genomic research on complex allotetraploid traits.…”
Section: Introductionmentioning
confidence: 99%
“…Mutants of Brachypodium, an emerging plant model, are available at the Joint Genome Institute (T-DNA, chemical, and radiation mutants (Fitzgerald et al, 2015;Raissig and Woods, 2022). Additional mutant libraries were further produced for numerous plants, including tobacco (Julio et al, 2008;Lewis et al, 2010;Lewis et al, 2015Takakura et al, 2018Udagawa et al, 2020;Zhao et al, 2020), tomato (Saito et al, 2011), rice (Meng et al, 2017), or cotton (Lian et al, 2020).…”
Section: Insect Dietmentioning
confidence: 99%